Distinctive Association of the Functional Connectivity of the Posterior Cingulate Cortex on Memory Performances in Early and Late Amnestic Mild Cognitive Impairment Patients - Kang, Dong Woo; Wang, Sheng-Min; Um, Yoo Hyun; Na, Hae-Ran; Kim, Nak-Young; Lee, Chang Uk; Lim, Hyun Kook (Frontiers in Aging Neuroscience, 2021)
Background: Attempts have been made to explore the biological basis of neurodegeneration in the amnestic mild cognitive impairment (MCI) stage, subdivided by memory performance. However, few studies have evaluated the differential impact of functional connectivity (FC) on memory performances in early and late MCI patients. Objective: To explore the difference in functional connectivity of the posterior cingulate cortex (PCC) among healthy controls (HC) (n=37), early (n=30), and late MCI patients (n=35) and to evaluate a group-memory performance interaction against the FC of PCC. Methods: Subjects underwent resting-state functional MRI scanning and a battery of neuropsychological tests. Results: A significant difference among the three groups was found in functional connectivity between the PCC (seed region) and bilateral crus cerebellum, right superior medial frontal gyrus, superior temporal gyrus, and left middle cingulate gyrus (Monte Carlo simulation corrected p < 0.01, cluster p < 0.05). Additionally, early MCI patients displayed higher FC values than the HC and late MCI patients in the right superior medial frontal gyrus, cerebellum crus 1, and left cerebellum crus 2 (Bonferroni corrected p < 0.05). Furthermore, there was a significant group-memory performance interaction (HC vs. early MCI vs. late MCI) for the FC between PCC and bilateral crus cerebellum, right superior medial frontal gyrus, superior temporal gyrus, and left middle cingulate gyrus (Bonferroni corrected p < 0.05). Conclusions: These findings contribute to the biological implications of early and late MCI stages, categorized by evaluating the impairment of memory performance. Additionally, comprehensively analyzing structural differences in the subdivided amnestic MCI stages could deepen our understanding of these biological meanings.